Olfactory Delusional Syndrome and Intracranial Meningioma. (30th May 2011) - Rotondo, Michele; Natale, Massimo; D'Avanzo, Raffaele; Scuotto, Assunta
Abstract : We report the case of a 37-year-old female in which the removal of a suprasellar neoplasm was accompanied by the disappearance of a longstanding olfactory delusion syndrome. In primary care the patient condition was exclusively thought to be psychic in origin, neglecting the possible, not infrequent, organic contribution. The delayed diagnosis produced neurological impairment, only partially recovered after surgical therapy. This case might help to improve the patient management via multi-specialist cooperation and to broaden the knowledge about somatic mechanisms of psychic disturbances, are not often taken into account.